HUBUNGAN PENGETAHUAN TENTANG KESEHATAN GIGI DENGAN PERILAKU PERAWATAN GIGI PADA ANAK USIA SEKOLAH DI SDN 009 TAMBUSAI - handayani, eka yuli; wulandari, sri; fitria, rahmi (Jannatul Makwa Health : Jurnal Ilmiah Kesehatan (Scientific Journal of Health), 2023)
Dental health problems in children can be very serious problems such as pain, heart defects, kidney and stomach infections, malnutrition, learning concentration disorders and death. The results of Basic Health Research (2018) state that in Indonesia, as many as 94.7% brush their teeth every day, namely in the age range ≥ 3 years, but 2.8% carry out proper dental care, namely morning and evening. The purpose of this study was conducted to determine the relationship between knowledge about dental health and dental care behavior in school-age children at SDN 009 Tambusai. The research method is descriptive correlation with a population of 74 respondents and using a total sampling of 74 children aged 2 and 3 at SDN 009 Tambusai. The results of this study were found that the most knowledge of students about dental health care was sufficient as many as 35 people (47.3%), student behavior regarding dental health care was bad as many as 43 people (58.1%). The statistical test results obtained P value = 0.002 (<0.05) meaning that there is a relationship between knowledge about oral health and dental care behavior in school-age children at SDN 009 Tambusai.